2017
DOI: 10.1108/h-10-2016-0080
|View full text |Cite
|
Sign up to set email alerts
|

Impact of perceived corporate social responsibility on attitudes and behaviors of pharmacists working in MNCs

Abstract: Purpose This study aims to find out how corporate social responsibility (CSR) initiatives are perceived by pharmacists and how it influences employees’ organizational commitment and organizational citizenship behavior (OCB) and role of perceived supervisor support in the study. Design/methodology/approach Pharmacists of different hierarchical levels from five multinational pharmaceutical industries in Pakistan were selected as study samples. Data were collected from 136 pharmacists working in Punjab Region. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 56 publications
(64 reference statements)
1
13
0
Order By: Relevance
“…Consistent with theoretical considerations, the nine hypothesised model was significant. The main results were strongly supported by recent studies (Gharleghi et al , 2018; Hur et al , 2018; Khaleel et al , 2017; Lee et al , 2013). Intrapreneurship outcomes are related to firm performance at both macro- and micro-levels (Åmo and Kolvereid, 2005; Antoncic and Hisrich, 2003; Covin and Slevin, 1991; Criado-Gomis et al , 2018; Fellnhofer et al , 2017; Kollmann et al , 2017; Kuratko et al , 2013; Pinchot, 1985; Urban and Wood, 2017; Zahra and Covin, 1995).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Consistent with theoretical considerations, the nine hypothesised model was significant. The main results were strongly supported by recent studies (Gharleghi et al , 2018; Hur et al , 2018; Khaleel et al , 2017; Lee et al , 2013). Intrapreneurship outcomes are related to firm performance at both macro- and micro-levels (Åmo and Kolvereid, 2005; Antoncic and Hisrich, 2003; Covin and Slevin, 1991; Criado-Gomis et al , 2018; Fellnhofer et al , 2017; Kollmann et al , 2017; Kuratko et al , 2013; Pinchot, 1985; Urban and Wood, 2017; Zahra and Covin, 1995).…”
Section: Discussionsupporting
confidence: 83%
“…The pharmaceutical sector is regarded as the significant sensitive to the impact of CSR because an outstanding feature of this industry is that it is the subject to more diverse and complex stakeholders than the most other sectors of the economy (Zaharia, 2011). Pharmaceutical firms need to be socially responsible to build up their reputation, which affects attracting and motivating proactive employee behaviours for sustainable competitiveness (Khaleel et al , 2017). Despite this broad research interest, indeed few recent studies were focusing on internal CSR practices and stakeholders in the pharmaceutical sector.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to waste minimization, sustainable corporate growth has a significant effect on productivity. It is closely linked with CSR stakeholders' satisfaction ( Khaleel et al, 2017 ). CSR-engaged businesses strategically keep improving their image and build outstanding ties with shareholders that effectively improve their business performance ( McWilliams and Siegel, 2001 ; Turban and Greening, 1997 ; Davis, 1973).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Zhang et al (2016) found that AC mediated Kim and Mauborgne (1993), Johnson et al (2002), Hitotsuyanagi-Hansel et al (2016) the relationship between employees' trust in supervisor and intention to leave, and between employees' job satisfaction and intention to leave. Recently, Khaleel, Chelliah, Rauf, and Jamil (2017) found support for the mediating role of AC in the relationship between corporate social responsibility and OCBs. Wong and Wong (2017) further demonstrated the mediating role of AC in the relationship between perceived organizational support and turnover intention, and job security and turnover intention.…”
Section: Organizational Commitment As Moderator and Mediatormentioning
confidence: 99%
“…Outcomes are categorized in terms of job attitudes and job behaviors. Moderators are classified in terms of culture, leadership and HR practices and Khaleel, Chelliah, Rauf, and Jamil (2017), Wong and Wong (2017) demographics. Figure 1 provides an illustrative summary of prior research on OC in MNCs.…”
Section: Summary Of Review and Future Research Agendamentioning
confidence: 99%